Konsep Syuro dalam Perspektif Islamic Worldview - Zein, Fuad Muhammad (POLITEA, 2019)
Syuro has an important role in Islam. As a decision-making mechanism, syuro plays an important role in every aspect of human life. Syuro is also understood as an appreciation of the freedom of expression of human beings in social relations. Therefore, the true syuro in Islam is not always identical to politics. It's just that, as a large part of human life, the role of politics in social life is also very important. As a means of upholding shari'a, politics is considered capable of providing good legal certainty for human social life and also in determining a political leader. Due to these interests, the role of syuro in politics cannot be avoided. Syuro in Islamic politics cannot be directly equated with the practice of deliberation in the current political phenomenon. In addition to the uniqueness of the concept that emphasizes respect for human dignity in terms of his freedom, syuro in Islam places great emphasis on scientific authority, syuro in Islam is also not always identical with the concept of majority rule, because the basis is sharia. So if the majority opinion is contrary to what is in sharia, then the majority opinion is not acceptable.